2016
DOI: 10.1111/1754-9485.12428
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated versus conventionally fractionated radiotherapy for ductal carcinoma in situ (DCIS) of the breast

Abstract: Introduction Hypofractionated radiotherapy (RT) in the setting of early invasive breast cancer has been shown to have similar local control rates and cosmetic outcomes as conventionally fractionated RT. This study compares ipsilateral recurrence rates between hypofractionated and conventional RT, with and without a boost. The effect of hypofractionated RT and chest wall separation (CWS) on cosmetic outcome was also assessed. Methods All patients with ductal carcinoma in situ (DCIS) treated between 1998 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Our study found that 93-100% of patients had grade 0 to 1 acute and late toxicities. These results are in line with the skin toxicity finding reported in other retrospective studies (6)(7)(8)12,13) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study found that 93-100% of patients had grade 0 to 1 acute and late toxicities. These results are in line with the skin toxicity finding reported in other retrospective studies (6)(7)(8)12,13) .…”
Section: Discussionsupporting
confidence: 92%
“…In terms of cosmesis, 93% of the patients who reached the 6-month follow-up visit had excellent to good cosmetic outcomes, which is consistent with a previous report of 92.9% (8) . The two patients (6.9%) who noted only a fair cosmetic result had a breast volume of more than 1,000 cc, although this reflected 33% of all the patients with a large breast volume (> 1,000 cc).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This paper involved a comprehensive analysis of 35 studies [ 5 , 8 , 14 , 16 , 24 54 ] comprising a total of 18,246 patients who had been diagnosed with breast cancer. The sample consisted of 13 randomized controlled trials with a Jadad score exceeding 4 and 22 retrospective studies with a Newcastle–Ottawa Scale score of 6 or higher.…”
Section: Resultsmentioning
confidence: 99%